Experimental study of dual-wavelength laser generation in Ytterbium-doped fiber / Muhammad Aizi Mat Salim - Muhammad Aizi , Mat Salim (2018)
This thesis describes the research work that has been carried out on generating dual-wavelength fiber lasers (DWFLs) in the one micron waveband-based ytterbium-doped fiber as an active medium. Various devices were used, including dual-tapered microfiber-based Mach-Zehnder Interferometer (MZI), Side Polished Fiber (SPF), and strain technique was discussed in DWFLs operation with regard to stability, tunability, output power and Side Mode Suppression Ratio (SMSR). A stable Single Longitudinal Mode (SLM) DWFL was successfully demonstrated by employing 2 μm diameter of dual-tapered microfiber MZI with SMSR of 50 dB and wavelength spacing of 0.94 nm. Then, by employing dual-tapered microfiber and tunable band pass filter (TBPF) together, the narrowest wavelength spacing of DWFL was obtained with 0.06 nm and SMSR of 50dB. Another dual-tapered microfiber with diameter of 10μm was positioned between xyz-translation stages, and then a strain was applied on the microfiber by tuning the micrometer driver. As a result, stable four sets of DWFLs were obtained at displacements from 2 to 190μm, and these outputs remained consistent after repeated several times. The SPF was also employed into the ring cavity to generate 3 sets of DWFLs with wavelength spacing of 6.89nm, 16.28nm and 22.16nm by adjusting the polarization controller (PC). While in pulse generation of DWFL, both wavelength selective filters and saturable absorbers (SAs) were employed together in the ring cavity to generate dual-wavelength and passively Q-switched operation simultaneously. The wavelength selective filters were dual-tapered microfiber MZI and SPF whereas the saturable absorbers (SAs) used were molybdenum diselenide (MoSe2), black phosphorus (BP), titanium dioxide (TiO2) and zinc oxide (ZnO). The SAs used in our experiments were shown to be new, potentially high quality saturable absorbers. Molybdenum diselenide as SA was used to generate passively Q-switched in DWFL based dual-tapered microfiber MZI. The obtained Q-switched based MoSe2 had a repetition rate ranging from 15.3 to 35.2 kHz. DWFL based microfiber Q-switched using BP as SAs was successfully demonstrated with tunable repetition rate from 6.5 to 62.5 kHz. Likewise, a passively Q-switched dual-wavelength YDFL using a titanium dioxide as SA and SPF as a wavelength selective filter had a repetition rate from 31.2 to 64.5 kHz. Lastly, zinc oxide together with SPF was proven in generating dual-wavelength passively Q-switched with a repetition rate from 67.6 to 104.2 kHz. The tunable repetition rate, output power, pulse energy and pulse width, and have been discussed in Q-switched operation.